Review of David Ferris. 2000. Schumann’s Eichendorff “Liederkreis” and the Genre of the Romantic Cycle. Oxford and New York: Oxford University Press - Kramer, Richard (Current Musicology, 2002)
To contend that Schumann “viewed the construction of musical meaning as an interactive process” is, first of all, to suggest that Schumann sets himself apart from his contemporaries in this endeavor-that he is unusual in this regard. This in itself should raise suspicions. But that’s the least of it. It doesn’t take much imagination to suppose that a composer (Schumann, if you like) might anticipate that his works will elicit a response, and that the act of responding will constitute in some cases a critical act, even a performerly one. But Ferris wishes us to believe that Schumann composed as though the meaning of his works were a function of some “interactive process,” by which must be meant a collaborative dialogue engaging any number of interlocutors with Schumann’s text, and all that such a text implies of some shadowy authorial presence. However we think to parse such interactivity in our own minds, it would be helpful to allow that if there is something of significance to be heard in Schumann’s Eichendorff Liederkreis, this significance must be immanent in all hearings of it, and that the way in which we construe the music is a function of what is signified. The subjectivity, it seems to me, resides in the music, even as it sets off sympathetic vibrations in those who must contend with it. I think I know what Ferris is getting at. Schumann’s cycle, in tune with much Romantic music, intones hermeneutical riddles. To engage the riddling means less to solve a mystery than to apprehend something of its obscure complexity: not to dissolve an ambiguity, but to take some pleasure in the discomfort that it arouses. For Ferris, this “interactive process” means to insinuate a compositional strategy. As a critical strategy, as a way of contending with the dialogics of text and reader” such “interactivity” makes some sense. For the composer, it is hollow.